Altered brain activity and functional networks in school‐age boys with severe haemophilia A: A resting‐state functional magnetic resonance imaging study. Issue 4 (3rd May 2022) - Hu, Di; Liu, Jingran; Liu, Guoqing; Hu, Shasha; Li, Zekun; Wei, Yunyun; Zhang, Ningning; Wu, Runhui; Peng, Yun
Abstract: Introduction: Microstructural alterations of brain structure in haemophilic boys were found in our previous study. Aim: We investigated alterations of brain function in school‐age boys with severe haemophilia A (HA) with resting‐state functional magnetic resonance imaging (rs‐fMRI). Methods: We obtained rs‐fMRI scans from 24 boys with HA and 25 demographically matched healthy children. Spontaneous brain activity parameters were calculated. Graph theoretical analyses on rs‐fMRI data at the global and regional levels were performed. Two‐sample t tests were used to analyze differences, and correlation analyses identified relationships between altered neural properties and psychological characteristics. Results: Children with severe HA showed small‐worldness organization but with an increased efficiency and compactness in functional segregation. The whole brain showed an overtight connection pattern. At the regional level, significantly increased nodal efficiency in the salience network (SN), default mode network (DMN) and executive control network was found. Social Anxiety Scale for Children (SASC) scores were positively correlated with these alterations. Spontaneous brain activity alterations in regions including the cerebellum, frontal gyrus (orbital part), temporal gyrus and thalamus were observed; some of these regions have been closely related to social anxiety and family or social support. Conclusion: Our study is the first to evaluate the neurological functional changes in school‐age boys with severe HA. Disruptions in topographic characteristics and abnormal activity were closely related to social conditions. These data could help us to understand early neurological alterations in haemophilic children, improve the traditional view of family support and strengthen normal school life at an early stage.